2021
DOI: 10.21608/jfds.2021.222019
|View full text |Cite
|
Sign up to set email alerts
|

Organic Propolis Extract as a Natural Fortifier and Preservative for Milk

Abstract: Natural materials that can be used as preservatives in the food sector have become very important. Propolis is getting a lot of attention due to its antioxidant and antibacterial properties. The objectives of this paper was to see if organic propolis extract could be used as a natural preservative and fortifier in raw and pasteurised milk storage. Propolis extracts were employed at two different concentrations (0.5 and 1 %) to test their impact. T.S., pH, Titratable acidity, colour, Total flavonoid, and total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…These results are in agreement with [41], and this is due to that milk is free of all microbes from its creation until its exit from the udder of disease-free cows, but its unique composition, rich in all nutrients, makes it an ideal growth environment for microbes [42]. Despite that, the same time the data indicated that (RM), (EM) and (CM) were completely free of coliform bacteria (-), and these results are consistent with [43,44], said that milk is free of coliform bacteria except when contaminated with human feces or sewage. In addition, pH of raw milk and concentrated milk (evaporated or concentrated milk) ranges between 6.5-6.7 and 5.8-6.6 respectively, which is suitable for the growth of molds and yeasts and spore-forming bacteria because it bears a wide range of pH 4-7,while coliform bacteria need pH up to 4.4 at most [45].…”
Section: Microbiological Quality Of Raw Evaporated and Concentrated Milksupporting
confidence: 58%
“…These results are in agreement with [41], and this is due to that milk is free of all microbes from its creation until its exit from the udder of disease-free cows, but its unique composition, rich in all nutrients, makes it an ideal growth environment for microbes [42]. Despite that, the same time the data indicated that (RM), (EM) and (CM) were completely free of coliform bacteria (-), and these results are consistent with [43,44], said that milk is free of coliform bacteria except when contaminated with human feces or sewage. In addition, pH of raw milk and concentrated milk (evaporated or concentrated milk) ranges between 6.5-6.7 and 5.8-6.6 respectively, which is suitable for the growth of molds and yeasts and spore-forming bacteria because it bears a wide range of pH 4-7,while coliform bacteria need pH up to 4.4 at most [45].…”
Section: Microbiological Quality Of Raw Evaporated and Concentrated Milksupporting
confidence: 58%
“…Shaban and Galal [100] investigated the fortification and preservative ability of PE in raw and pasteurized milk. Milk's organoleptic properties were not affected.…”
Section: Dairymentioning
confidence: 99%
“…Parmar et al (2018) demonstrated that the concentrated milk had a chroma value of 9. A previous work reported chroma values of 9.39 and 9.06 for FM and pasteurized milk (Shaban et al, 2021).…”
Section: Resultsmentioning
confidence: 92%
“…The current results were close to those reported by Parmar et al (2018), who disclosed that concentrated milk had a C value of 9. Another study (Shaban et al, 2021) declared that the C * value of pasteurized milk ranged between 8.71 and 9.06. The reduced cubic model can be used to predict the C value at different values of EFI and MFR (Table S1).…”
Section: Resultsmentioning
confidence: 99%